2019
DOI: 10.1038/s41550-018-0611-0
|View full text |Cite
|
Sign up to set email alerts
|

Observational constraints on the feeding of supermassive black holes

Abstract: Supermassive Black Holes grow at the center of galaxies in consonance with them. In this review we discuss the mass feeding mechanisms that lead to this growth in Active Galactic Nuclei (AGN), focusing on constraints derived from observations of their environment, from extragalactic down to galactic and nuclear scales. At high AGN luminosities, galaxy mergers and interactions play an important role in AGN triggering and feeding. However, gas chaotic cold accretion in galaxy clusters can trigger radiatively ine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 145 publications
(82 citation statements)
references
References 233 publications
(262 reference statements)
9
67
0
Order By: Relevance
“…The above results are in agreement with those of previous studies by our AGNIFS group, in which we have additionally reported, for H 2 , the presence of inflows in a number of galaxies. We have also found that outflows are most easily seen in the ionized gas (Storchi-Bergmann & Schnorr-Müller 2019) and that this gas shows a more centrally concentrated flux distribution than that of H 2 Riffel et al (2018), also in agreement with what we found in the present paper.…”
Section: Gas Kinematicssupporting
confidence: 92%
“…The above results are in agreement with those of previous studies by our AGNIFS group, in which we have additionally reported, for H 2 , the presence of inflows in a number of galaxies. We have also found that outflows are most easily seen in the ionized gas (Storchi-Bergmann & Schnorr-Müller 2019) and that this gas shows a more centrally concentrated flux distribution than that of H 2 Riffel et al (2018), also in agreement with what we found in the present paper.…”
Section: Gas Kinematicssupporting
confidence: 92%
“…The feeding of SMBHs begins with materials accretion at extragalactic scales, which subsequently passes through galactic and nuclear scales to the broad-line region (BLR) and accretion disk before falling into the black hole Article number, page 1 of 30 arXiv:1912.07734v1 [astro-ph.GA] 16 Dec 2019 A&A proofs: manuscript no. aanda or being ejected by jets or winds (Storchi-Bergmann & Schnorr-Müller 2019). The materials in the host galaxy residing near the nucleus can be ionized by radiation (e.g., Davidson 1972;Netzer 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore understanding the mechanisms that are involved in transferring the gas from kiloparsec to sub-parsec scales is crucial (e.g. recent review of Storchi-Bergmann & Schnorr-Müller 2019).…”
Section: Introductionmentioning
confidence: 99%